A natureza da comunicação bios midiática - Cimino, Laura Fernanda (2010)
One of the recurring themes in the reported studies comunicative has been the possibility of proposing another way of dealing with communication that is able to understand the recent changes in the culture caused by the new instrumental technologies of social virtual. This study therefore is to investigate how to structure those bonds mediated by the spread of the virtualization of everyday experience and that currently result from communication media bios (conceptual metaphor used by Muniz Sodré to designate new forms of life and socialization driven by the current stage of cognitive capitalism). In other words, this research seeks to analyze and interpret the ontological character of interactive links which are reflected in real time and space self-referential and, therefore, will give the specific internal communicative action. Hence, our hypothesis is that the communication capacity of a medium is directly related to how the operating systems (codes) are organized into the various complex communicative (language). In this sense, self-referentiality of digital media for interfering in the production and distribution of informative content, while it changes the meaning of communicative procedures by means of another diagram of communicating that occurs in a continuous way and evolutionary designing a mapping between culture and ecological environment. This fact has led us to other parameters epistemological who see the bios of the media, despite its vagueness and weaknesses as an object of study, as a new, potentially capable of promoting an ecological science of communication nowadays